Identification of parotid salivary biomarkers in Sjögren's syndrome by surface-enhanced laser desorption/ionization time-of-flight mass spectrometry and two-dimensional difference gel electrophoresis - Ryu, O. H.; Atkinson, J. C.; Hoehn, G. T.; Illei, G. G.; Hart, T. C. (Rheumatology (Oxford, England), 2006)
To identify the most significant salivary biomarkers in Sjögren's syndrome (SS) using proteomic methods. Parotid saliva from 20 non-SS subjects and 41 primary SS patients was analysed. Protein expression profiles for each sample were generated by surface-enhanced laser desorption/ionization time-of-flight-mass spectrometry (SELDI-TOF-MS). Mean peak intensities of SS patients and non-SS subjects were compared by univariate analyses. Samples pooled by diagnosis (SS and non-SS) and labelled with different Cy dyes were compared by two-dimensional difference gel electrophoresis (2D-DIGE). Two protein levels that were most significantly different by SELDI-TOF-MS and 2D-DIGE were validated by enzyme-linked immunosorbent assay in individual samples. SELDI-TOF-MS of 10-200 kDa peaks revealed eight peaks with >2-fold changes in the SS group that differed from non-SS at P < 0.005. Peaks of 11.8, 12.0, 14.3, 80.6 and 83.7 kDa were increased, while 17.3, 25.4, and 35.4 kDa peaks were decreased in SS samples. 2D-DIGE identified significant increases of beta-2-microglobulin, lactoferrin, immunoglobulin (Ig) kappa light chain, polymeric Ig receptor, lysozyme C and cystatin C in all stages of SS. Two presumed proline-rich proteins, amylase and carbonic anhydrase VI, were reduced in the patient group. Three of these ten biomarkers have not been associated previously with SS. The salivary proteomic profile of SS is a mixture of increased inflammatory proteins and decreased acinar proteins when compared with non-SS. Future studies will test the ability of these biomarker levels, alone and in combination, to diagnose the salivary component of SS.